PfHDAC1 is an essential regulator of P. falciparum asexual proliferation and host cell invasion genes with a dynamic genomic occupancy responsive to artemisinin stress - Abhishek Kanyal; Bhagyashree Deshmukh; Heledd Davies; D. V. Mamatharani; Dilsha Farheen; Moritz Treeck; Krishanpal Karmodiya (mBio, 2024)
ABSTRACT Plasmodium falciparum, the deadly protozoan parasite responsible for malaria, has a tightly regulated gene expression profile closely linked to its intraerythrocytic development cycle. Epigenetic modifiers of the histone acetylation code have been identified as key regulators of the parasite’s transcriptome but require further investigation. In this study, we map the genomic distribution of Plasmodium falciparum histone deacetylase 1 (PfHDAC1) across the erythrocytic asexual development cycle and find it has a dynamic occupancy over a wide array of developmentally relevant genes. Overexpression of PfHDAC1 results in a progressive increment in parasite load over consecutive rounds of the asexual infection cycle and is associated with enhanced gene expression of multiple families of host cell invasion factors (merozoite surface proteins, rhoptry proteins, etc.) and with increased merozoite invasion efficiency. With the use of class-specific inhibitors, we demonstrate that PfHDAC1 activity in parasites is crucial for timely intraerythrocytic development. Interestingly, overexpression of PfHDAC1 results in decreased sensitivity to frontline-drug dihydroartemisinin in parasites. Furthermore, we identify that artemisinin exposure can interfere with PfHDAC1 abundance and chromatin occupancy, resulting in enrichment over genes implicated in response/resistance to artemisinin. Finally, we identify that dihydroartemisinin exposure can interrupt the in vitro catalytic deacetylase activity and post-translational phosphorylation of PfHDAC1, aspects that are crucial for its genomic function. Collectively, our results demonstrate PfHDAC1 to be a regulator of critical functions in asexual parasite development and host invasion, which is responsive to artemisinin exposure stress and deterministic of resistance to it.IMPORTANCEMalaria is a major public health problem, with the parasite Plasmodium falciparum causing most of the malaria-associated mortality. It is spread by the bite of infected mosquitoes and results in symptoms such as cyclic fever, chills, and headache. However, if left untreated, it can quickly progress to a more severe and life-threatening form. The World Health Organization currently recommends the use of artemisinin combination therapy, and it has worked as a gold standard for many years. Unfortunately, certain countries in southeast Asia and Africa, burdened with a high prevalence of malaria, have reported cases of drug-resistant infections. One of the major problems in controlling malaria is the emergence of artemisinin resistance. Population genomic studies have identified mutations in the Kelch13 gene as a molecular marker for artemisinin resistance. However, several reports thereafter indicated that Kelch13 is not the main mediator but rather hinted at transcriptional deregulation as a major determinant of drug resistance. Earlier, we identified PfGCN5 as a global regulator of stress-responsive genes, which are known to play a central role in artemisinin resistance generation. In this study, we have identified PfHDAC1, a histone deacetylase as a cell cycle regulator, playing an important role in artemisinin resistance generation. Taken together, our study identified key transcriptional regulators that play an important role in artemisinin resistance generation.